Guano, compromisos creíbles y el pago de la deuda externa peruana del siglo XIX - Vizcarra, Catalina (2011)
Peru’s experience with sovereign debt during the guano boom is one of the most remarkable in the nineteenth century. Despite the country’s ongoing political instability and poor capital market reputation, the price of Peruvian bonds soared shortly after settlement in 1849, and the country enjoyed relatively low credit risk until the 1870. The paper discusses the incentives Peru and its creditors faced, and explains how Peru’s extraordinary performance was founded on its credible commitment to service its debt with the guano proceeds